Development of the French version of the Davos Assessment of Cognitive Biases Scale in a non‐clinical sample of young adults. Issue 2 (31st March 2022) - Livet, Audrey; Pétrin‐Pomerleau, Philippe; Pocuca, Nina; Afzali, Mohammad H.; Potvin, Stephane; Conrod, Patricia J.
Abstract: Background: In accordance with continuum and cognitive behaviour models of psychosis, cognitive biases precede the onset and the maintenance of positive symptoms. The Davos Assessment of Cognitive Biases Scale (DACOBS), a self‐report measure, was developed to explore the prevalence of specific cognitive biases. This study aims to validate the French version of this instrument. Methods: We first translated the English version of the DACOBS into French. Then, using a sample of 213 French speaking young adults (mean age = 20.54, SD  = 1.65; 83% females), we examined the factor structure, internal consistency, concurrent, and convergent validities of the current version. Results: We found an 18‐item, four‐factor version of the French DACOBS comprising external attribution bias (five items), social cognition problems (five items), subjective cognition problems (five items), and safety behaviours (five items), provided best fit‐to‐data. Internal consistency for the resulting subscales ranged from acceptable to excellent (Cronbach's α range = .62–.86). All subscales were significantly, positively associated with a measure of psychotic‐like experiences and positively associated with established measures of theoretically relevant constructs, demonstrating concurrent and convergent validity of the French DACOBS. Conclusions: The French DACOBS is a reliable and valid and reliable instrument assessing cognitive biases, in a French‐speaking youth population. Ultimately, the French DACOBS may be used to identify at‐risk youth which may benefit from cognitive interventions targeting cognitive biases, safety behaviours and social cognition which could potentially prevent transition to psychosis in youth.